Cáscaras de piña y mango deshidratadas como fuente de fibra dietética en producción de galletas. - Cedeño Reyes, Jessenia Lisseth (2014)
This research presents an alternative processing and industrialization of pineapple and mango peels, to establish its dosage as a source of dietary fiber in the production of cookies, we evaluated the qualitative characteristics of the shells with the following results: HCW (holding capacity water) 4,0 cm³/g and 4,5 cm³/g; RCo (retention capacity oil) 3,5 cm³/g and 3,0 cm³/g; SC (swelling capability) 3,2 cm³/g and 5,1 cm³/g; ash 4,1% and 3,6%; protein 3,5% and 3,7%; moisture 9,8% and 6,7%; fat 0,47% and 2,93%; crude fiber 15,03% and 12,5%; total carbohydrates 44,2% and 51,8%; Energy 195 kcal and 248,7 kcal; total dietary fiber 37,9% and 31,23%, respectively. The treatments were made according to the following factors:% of shells (4, 8 and 12) and source of dietary fiber (pineapple shells and dried mango peels), we assessed the degree of acceptability of treatments with scoring test, by analysis of variance of two factors one single sample by group, Tukey p>0,05 and LSD was determined the significant differences in a2b1 and a3b2 treatments were evaluated in bromatological and microbiological properties: energy 448 kcal and 451 kcal; protein 8,17% and 7,76%; fat 19,5% and 20%; total dietary fiber 5,31% and 4,12%; total carbohydrate 59,83% and 59,60%; the analyzes were performed on a wet basis with 7,01% and 6,20%, respectively, without the presence of molds, yeasts and coliforms, meeting according to the standards set out by INEN 2085:05 and NMX-F-006-1983.